(untitled) (The Peerian Journal, 2022)
The article discusses the preparation of aminoaldehyde oligomers based on carbamide, urotropine and methacrylic acid, the conditions for the synthesis of oligomers, the dependence of the composition, molecular weight, mass fractions of the dry residue of oligomers on the synthesis conditions, on the duration of the process, on the ratios of the components